New combinations for nothotaxa of Populus (Salicaceae) from China - Shang, Ce; Zhang, Limei; Zhang, Zhixiang (Phytotaxa, 2016)
The extensive natural and artificial hybridization within the genus Populus Linnaeus (1753: 1034) has led to numerous hybrids, many of which have been formally described. The Flora of China (Fang et al. 1999) documented nine such hybrids at the rank of nothospecies. Three of these names are incorrect applying to their hybrid formulae according to the Appendix I of ICN (McNeill et al. 2012), and are corrected here.